PENGARUH GAYA KEPEMIMPINAN SITUASIONAL TERHADAP KINERJA KARYAWAN CV. ELANG MAS - B31109055, Susanto (Jurnal Manajemen Update, 2014)
The purpose of this study was to determine the influence of situational leadership on performance of employes at CV. Elang Mas in Pontianak. This study is a correlational research. Situational leadership of 2 variables, that is behavior supporting from leader (X1), and behavior directing from leader (X2), while performance as a Y variable. CV Elang mas has 37 employes, all of who were used as samples in this study. The data collected by using questionnaires with sampling technique using saturated sampling technique. This study using multiple regression analysis tools. Data were processed by using SPSS 18. The analysis shows from 2 variabels, only behavior supporting from leader has a significant influence on performance of employes at CV. Elang Mas, while variabels behavior performance directing from leader did not have a significant influence with performance of employes in CV. Elang Mas Kata Kunci : Gaya kepemimpinan situasional, Kinerja.